Peran Bea Dan Cukai Dalam Pengawasan Penyelundupan Narkotika Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean B Kualanamu - Berkat M.K. Siahaan; Suhaidi Suhaidi; Rizkan Zulyandi (Mahesa Research Center, 2023)
The purpose of this study was to analyze the legal arrangements regarding narcotics based on regulations in Indonesia, the role of customs and excise in conducting surveillance to prevent narcotics smuggling and the obstacles faced by the Kualanamu Airport Middle Type Customs and Excise Supervision and Service Office in supervising narcotics smuggling at Kualanamu Airport. The research method used is empirical law, namely empirical legal research studying law that is conceptualized as real behavior (actual behavior). The nature of the research used in this study is descriptive analysis. The study used two approaches, namely the statute approach and the case approach. The results of research on narcotics crime cases by applying Article 114 paragraph (2) and Article 112 paragraph (2) and Article 132 of the Law of the Republic of Indonesia No. 35 of 2009 concerning Narcotics The Role of the Customs and Excise Service Office of Middle Customs Type B Kualanamu. Kualanamu Customs and Excise continues to work together with the North Sumatra Regional Police, the National Narcotics Agency for North Sumatra Province, in order to eradicate the circulation of narcotics that enter Indonesian territory. Obstacles faced by officers include the lack of human resources, limited facilities and infrastructure, lack of public awareness of the importance of customs declarations.